Aristotle in the 20th Century Philosophy – A Form of Sickness or Therapy? - Bleja, Paweł (Peitho. Examina Antiqua, 2016)
E. Berti, Arystoteles w XX wieku, tłum. A. Dudzińska-Facca, D. Facca, Warszawa 2015, ss. 270.